2015
DOI: 10.1002/pssb.201451443
|View full text |Cite
|
Sign up to set email alerts
|

Ambipolar behavior of Te and its effect on the optical emission of ZnO:Te epitaxial thin film

Abstract: We present control over the ambipolar nature of Te in ZnO and the corresponding optical band gap in epitaxial thin film grown by pulsed laser deposition. Experimentally, the decrease in band gap is found to be strongly dependent on the Te concentration for TeO compared to TeZn. Emission at 3 eV for TeZn, irrespective of Te content is explained by first principle calculation considering Zn vacancy in the lattice. An experimental band bowing parameter of ∼7 eV is obtained for TeO and is in agreement with modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
3
1
2
Order By: Relevance
“…These emissions are due to V O and Schottky‐type‐I defects, respectively. Previous mbJGGA‐based band gap calculation already suggested that the emission at 2.73 eV is due to V O and the present calculation suggests that the emission at 2.45 eV is due to Schottky‐type‐I defects . The Schottky type of defects forms spontaneously upon annealing of ZnO with the attempt of rendering the film p‐type by reducing V O­ concentration, and thus kills the prospect to turn the film p‐type .…”
Section: Resultsmentioning
confidence: 47%
See 1 more Smart Citation
“…These emissions are due to V O and Schottky‐type‐I defects, respectively. Previous mbJGGA‐based band gap calculation already suggested that the emission at 2.73 eV is due to V O and the present calculation suggests that the emission at 2.45 eV is due to Schottky‐type‐I defects . The Schottky type of defects forms spontaneously upon annealing of ZnO with the attempt of rendering the film p‐type by reducing V O­ concentration, and thus kills the prospect to turn the film p‐type .…”
Section: Resultsmentioning
confidence: 47%
“…ZnO is a wide band gap semiconductor with a band gap of ∼3.37 eV and a strong exciton binding energy of 60 meV at room temperature . ZnO offers itself as an alternative candidate for the expensive GaN‐based light emitting diodes (LEDs) and various other bipolar junction‐based device technologies . However, p‐type doping remains elusive in this system.…”
Section: Introductionmentioning
confidence: 99%
“…Then the model of Zn 35 RH i O 35 (R = S/Se/Te) was constructed, as shown in Figure 1C. The doping amounts of S/Se/Te in the model constructed in this paper (1.39 mol%) are lower than the doping amount without phase transition used in the experiments carried out in several comparable studies in the literature [18][19][20]. The V Zn content in this paper is 2.78 mol%, which is much lower than the V Zn content of 9 mol% used in the experiments comprised in the studies of Wu et al [21] and Ghosh et al [22], and does not cause a phase change in the system.…”
Section: Model Constructionmentioning
confidence: 93%
“…Слои ZnO : Te/Si(111) осаждались при температурах 700−750 Следует отметить, что особенностью теллура при легировании ZnO является двуполярность, т. е. при замещении теллуром цинка валентность Te −2, а при замещении вакансий кислорода +4. Причем при замещении теллуром междоузельного цинка после отжига пленки остаются прозрачными, а если теллур замещает кислородные вакансии, то пленки имеют рыжеватую окраску [9]. В нашем случае наличие фазы ZnTe, сравнимой с ZnO, и рыжеватый оттенок пленки после отжига указывают на замещение теллуром кислорода в кристаллической решетке ZnO.…”
Section: методика экспериментаunclassified
“…Следует отметить, что дефектная полоса, обычно присутствующая в спектрах ФЛ ZnO c максимумом 505−520 nm, разрешилась на линию 483 nm в синей области спектра и 490, 520 nm в зеленой области спектра. Появление пика 483 nm обусловлено акцепторными вакансиями цинка, образующимися при избытке теллура в кристаллической решетке ZnO и приводящими к появлению фазы ZnTe x O 1−x [7,9]. Линии 490 и 520 nm в спектре люминесценции связаны с вакансиями кислорода и цинка соответственно [10].…”
Section: методика экспериментаunclassified